Analisis Hadith-hadith Zakat Dalam Karya Sahih al-Bukhari - Mohd Noor, Mohd Murshidi; Abdul Rahim, Ahmad Khilmy (Mufti of Federal Territory's Office, 2023)
Hadith is the second most important source in Islam after the Quran. Muslims have given hadith great attention since the early period of Islam. Usually, the works of hadith are only referred to from the point of view of the hadith and not from the point of view of Fiqh. If we want to understand hadith, the books are considered unsuitable for public reading because they are only raw material that has not been mixed to be used as a reference in Islamic Laws. However, the works of hadith are not separated from the discussions of Fiqh according to the scholars who compiled them such as Imam al-Bukhari. The translation of the chapter found in this work describes his works on the jurisprudence of hadith. This study utilizes qualitative research methods. Based on the importance of hadith in the discussion of Fiqh as emphasized by previous hadith scholars like Imam al-Bukhari, this article aims to obtain some views of scholars in their discussion on the understanding of the hadiths of zakat accumulated in Sahih al-Bukhari through the translation (tarjamah) of chapter by Imam al-Bukhari, which is considered still relevant to be discussed nowadays